A Biomechanical Comparison of 2 Over-the-Top Anterior Cruciate Ligament Reconstruction Techniques: A Cadaveric Study Using a Robotic Simulator. Issue 12 (14th December 2022) - Shiwaku, Kousuke; Suzuki, Tomoyuki; Shino, Konsei; Yamakawa, Satoshi; Otsubo, Hidenori; Okimura, Shinichiro; Suzuki, Daisuke; Nabeki, Shogo; Teramoto, Atsushi; Ohnishi, Hirofumi; Fujie, Hiromichi; Yamashita, Toshihiko
Background: For skeletally immature patients, over-the-top (OTT) anterior cruciate ligament (ACL) reconstruction (ACLR) is preferred. However, increased anterior laxity at deep knee flexion angles remains concerning. We modified the procedure to proximally shift the graft fixation site on the femur to prevent graft loosening at higher knee flexion angles and named it the supra-OTT procedure. Purpose: To compare anterior laxity and in situ forces of the ACL graft between conventional OTT and supra-OTT ACLR in a cadaveric model. Study Design: Controlled laboratory study. Methods: A total of 11 fresh-frozen cadaveric knee specimens underwent 4 robotic testing conditions: ACL intact, ACL resected, conventional OTT, and supra-OTT. For each condition, a 100-N load was applied at 0°, 15°, 30°, 60°, and 90° of knee flexion to simulate the Lachman test or anterior drawer test. In addition, a combined load of 5-N·m internal tibial torque and 10-N·m valgus torque was applied at 15° and 30° of knee flexion as a simulated pivot-shift test. Anterior tibial translation and in situ graft forces were recorded. The only difference between conventional OTT and supra-OTT ACLR was the graft fixation site on the femur. For conventional OTT ACLR, graft fixation was performed just on the proximal and lateral ends of the posterior condyle. For supra-OTT ACLR, the fixation point was around the proximal insertion of the lateral head of the gastrocnemius and the lateral edge of the posterior cortex, approximately 2 cm proximal to the conventional OTT position. Results: On the simulated anterior drawer test at 60° and 90° of knee flexion, anterior tibial translation after supra-OTT ACLR was significantly smaller than after conventional OTT ACLR ( P < .01). However, no significant differences were noted at other flexion angles or on the simulated pivot-shift test between the conventional OTT and supra-OTT procedures. Some overconstraint and higher graft forces were noted with both techniques, but the supra-OTT technique caused even more overconstraint at higher flexion angles. Conclusion: Supra-OTT ACLR showed better biomechanical performance to control anterior laxity than conventional OTT ACLR at higher knee flexion angles. Clinical Relevance: The supra-OTT procedure may improve anterior stability at deep knee flexion angles.